1999
DOI: 10.1046/j.1468-1331.1999.660685.x
|View full text |Cite
|
Sign up to set email alerts
|

Supression of cardiac parasympathetic functions in patients with right hemispheric stroke

Abstract: Supression of vagal parasympathetic activity was more apparent in stroke patients with right hemispheric lesions in our series. Therefore, the right hemisphere seems to have a greater effect upon parasympathetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…A clinical diagnosis and detailed medical history were carried out with special emphasis on types of AEDs taken, interictal EEG recordings, and cranial and hippocampal MRI. The epilepsy type was classified according to the recommendations of the International League Against Epilepsy (ILAE) [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A clinical diagnosis and detailed medical history were carried out with special emphasis on types of AEDs taken, interictal EEG recordings, and cranial and hippocampal MRI. The epilepsy type was classified according to the recommendations of the International League Against Epilepsy (ILAE) [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are indeed significant, since the decreased HRR at 1, 2 and 3 min after exercise is mainly a result of impaired vagal reactivation, a predictor of cardiovascular events [ 45 47 ]. Furthermore, decreased vagal tone is found in several conditions and it is generally associated with poor cardiovascular prognosis [ 48 50 ]. In fact, HRR after exercise seems to be correlated with heart rate variability in the early recovery phase after submaximal exercise [ 51 , 52 ], reinforcing our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Naver [ 29 ] indicated that heart rate variability entrained to deep breathing (a parasympathetic relationship) was reduced with right sided stroke, whereas peripheral sympathetic influences were equally distributed between the two sides. Sympathetic skin response and pulse rate variation (parasympathetic measure) were suppressed in patients with both right or left hemisphere lesions compared with controls [ 11 ]. This effect was more marked with right hemisphere lesions, although the authors failed to show a statistical difference when right and left sides were compared.…”
Section: Cerebral Lateralization Of Cardioregulatory Functionmentioning
confidence: 99%